On Properties of Magneto-dielectric Composites in the Effective Medium Approximation - A.T. Morchenko; L.V. Panina; S.V. Podgornaya; V.G. Kostishyn; P.A. Ryapolov (Журнал нано- та електронної фізики)
The development of ultra-broadband composite absorbers of electromagnetic waves depends largely on optimal combination of the medium characteristics that determine their absorption capacity and conditions for impedance matching and destructive interference. It is possible to achieve a higher absorption level in a wider frequency band by combining a variety of mechanisms enhancing the loss of electromagnetic field energy, for example, by combining specific constituents in a composite matrix. The analysis of various mixing models for constituent parameters is carried out in the effective medium approximation for ferrite-dielectric composites. It appears that the standard mixing rules do not explain the increase in the effective permittivity of ferrite composites in comparison with that of bulk ferrites. The proposed mechanism of such increase is based on the conductive properties of the ferrite granules and the equivalent capacitance effect. The developed model of permittivity calculation is based on the equivalent capacitor circuits and gives a satisfactory agreement with the experimental data.